Expression evolution in yeast genes of single-input modules is mainly due to changes in trans-acting factors - Wang, Daryi; Sung, Huang-Mo; Wang, Tzi-Yuan; Huang, Chih-Jen; Yang, Peggy; Chang, Tiffany; Wang, Yang-Chao; Tseng, Da-Lun; Wu, Jen-Pey; Lee, Tso-Ching; Shih, Ming-Che; Li, Wen-Hsiung (Genome Research, 2007)
Both cis- and trans-regulatory mutations contribute to gene expression divergence within and between species. To estimate their relative contributions, we examined two yeast strains, BY (a laboratory strain) and RM (a wild strain), for their gene-expression divergence by microarray. Using these data and published ChIP-chip data, we obtained a set of single-regulator-regulated genes that showed expression divergence between BY and RM. We randomly selected 50 of these genes for further study. We developed a step-by-step approach to assess the relative contributions of cis- and trans-variations to expression divergence by using pyrosequencing to quantify the mRNA levels of the BY and RM alleles in the same culture (co-culture) and in hybrid diploids. Forty genes showed expression divergence between the two strains in co-culture, and pyrosequencing of the BY/RM hybrid diploids showed that 45% (18/40) can be attributed to differences in trans-acting factors alone, 17.5% (7/40) mainly to trans-variations, 20% (8/40) to both cis- and trans-acting factors, 7.5% (3/40) mainly to cis-variations, and 10% (4/40) to cis-acting factors alone. In addition, we replaced the BY promoter by the RM promoter in each of 10 BY genes that were found from our microarray data to have expression divergence between BY and RM, and in each case our quantitative PCR analysis revealed a cis effect of the promoter replacement on gene expression. In summary, our study suggests that trans-acting factors play the major role in expression evolution between yeast strains, but the role of cis variation is also important.